TimeSPOT developments on charged-particle silicon sensors for high intensity 4D-Tracking - Lai, A. (Frontiers in Sensors, 2025)
This paper provides a comprehensive overview of recent advances in silicon sensors designed for 4D tracking. These devices are of particular relevance for the next-generation of high intensity collider experiments, where meeting stringent requirements in both spatial and temporal resolution, along with unprecedented levels of radiation hardness, will be crucial. Among the various sensor technologies under development, 3D silicon sensors have demonstrated the potential to satisfy all key performance criteria. The paper discusses the development and fabrication processes of these sensors, emphasizing their capability to deliver exceptional timing resolution and radiation tolerance. Methods adopted for their characterization and results obtained from recent experimental campaigns are presented and critically analyzed. Furthermore, the pivotal role of readout electronics in enabling high-precision timing performance is underscored.